Indirect Financing, membership to social security installments and the consequences to social security (Gestão & Regionalidade, 2023)
The practice of indirect financing through social security contributions together with the expectation regarding the launch of the fiscal recovery plans, are motivators of this article. The research aimed to verify if the adherents to the Special Tax Regularization Plan-PERT / 2017 presented financial difficulties to timely payment. The program covers 184,547 concessions and a debit amount of R $ 9,550,498,343.03. The investigation covered the hundred companies with the highest social security debts and occurred through the revenues earned and the results obtained by the companies at a time close to PERT / 2017 between 2014 and 2018. As methodological tools are the ABC Curve and the Analysis of Conglomerates. The practice of indirect financing was found, as 71% of the companies earned significant revenues, and 51% resulted in profits. As a contribution, the research brings a reflection on the equal treatment of defaulters, whose profiles are very different.
Keywords: Indirect financing. Social security installments. Installment programs.